Systematic Literature Review: Weaknesses and Strengths of the Latest Diagnostic Methods for COVID-19 - Putra, I Gusti Ngurah Dwija (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
SARS-CoV-2 is a positive-stranded RNA virus, the seventh coronavirus known to infect humans. Given the infectious nature of SARS-CoV-2 and its wide-reaching effects, finding a valid treatment is a top global priority. Although several vaccines have been used, the uncertainty remains unpredictable. Considering this, early diagnosis of SARS-CoV-2 is a prerequisite for effective containment and timely treatment, allowing doctors to intervene to prevent further spread and disease worsening. This study aims to provide references regarding the advantages and disadvantages of currently developing Covid-19 detection. This research is a Systematic Literature Review (SLR). The database analyzed in this study is in the 2019-2022 timeframe obtained from Google Scholar sources using Harzing's Publish or Perish for Windows version 8 search engine. Based on an article review, the Covid-19 detection test kits are grouped into 3, namely: acid-based detection methods nucleic acid (RT-PCR, dPCR, mNGS, RT-LAMP, CRISPR), serology-based detection methods (ICG/GICA, CLIA, ELISA, LFIA), and diagnostic CT imaging. Each method developed has its advantages and disadvantages. RT-PCR has always been the gold standard for detection. Other diagnostic techniques are also useful. Their combined results can exclude false negatives and positives as much as possible.